2012
DOI: 10.3813/aaa.918532
|View full text |Cite
|
Sign up to set email alerts
|

Sound Quality Evaluation of Hand-Held Power Tools

Abstract: Sound quality evaluation in the context of product sound quality has been addressed and investigated on hand-held power tools. Out of those, power drills, hand-held circular saws and jigsaws have been chosen as the products of interest. As eries of listening tests has been conducted in order to ascertain howp eople perceive not only the sound emitted by these devices in operation, buta lso certain properties of the devices themselves, such as their quality,s afety of handling, robustness, proper functioning an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…In any case, a wide range of sound power of various engines running in three different regimes results in the observed changes in sound pressure level and loudness and is expected to have a profound influence on the perception of these sounds. The values of Zwicker sharpness are generally lower than the ones observed in previous studies on the machinery-generated noise [21]. In this case the contribution of low frequency content to the overall spectrum is considerable, whereas in previous research the low frequency content of investigated sounds was negligible.…”
Section: Objective Analysiscontrasting
confidence: 76%
“…In any case, a wide range of sound power of various engines running in three different regimes results in the observed changes in sound pressure level and loudness and is expected to have a profound influence on the perception of these sounds. The values of Zwicker sharpness are generally lower than the ones observed in previous studies on the machinery-generated noise [21]. In this case the contribution of low frequency content to the overall spectrum is considerable, whereas in previous research the low frequency content of investigated sounds was negligible.…”
Section: Objective Analysiscontrasting
confidence: 76%
“…Similar findings have been obtained in product sound quality research focused on hand-held power tools. 27 The comparison of results of objective and subjective investigation reveals the importance of introducing the context into soundscape research. An example can be given by analyzing the results obtained for the park, where the value of the equivalent A-weighted sound pressure level reaches 58 dBA, in contrast with the Sea Organ, where it reaches 63 dBA.…”
Section: Discussionmentioning
confidence: 99%
“…Fastl () determined that loudness dramatically affects user preference when manipulating the loudness of electric‐razor sounds. Other researchers revealed that louder car‐engine sounds reduce comfort and elicit annoyance (Horvat, Domitrovi, & Jambrošić, ; Västfjäll et al, ), although such sounds can provide a sporty impression (Coen et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Roughness is described as buzzing and harsh sounds, evoking unpleasant and annoying feelings (Coen et al, ; Horvat et al, ). Meanwhile, roughness gives positive effects on activation, which is positively related to user preference on interior aircraft sounds (Västfjäll et al, ).…”
Section: Literature Reviewmentioning
confidence: 99%